2000
DOI: 10.1136/bmj.320.7242.1102
|View full text |Cite
|
Sign up to set email alerts
|

Educational differences in smoking: international comparison

Abstract: dementia in general to any substantial extent. If anything, persistent smoking may increase rather than decrease the onset rate of dementia, but any net effect on severe dementia cannot be large in either direction.We thank the British doctors some of whom have continued to collaborate in this prospective study of their health for almost half a century, Robert Clarke, Rory Collins, and Christina Davies for their comments, and Cathy Harwood and Gale Mead for preparing the manuscript.Contributors: RD planned the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
334
6
28

Year Published

2001
2001
2018
2018

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 526 publications
(394 citation statements)
references
References 20 publications
26
334
6
28
Order By: Relevance
“…Specifically, the prevalence of smoking was quite low among the population aged ⩾65 years before the crisis and this has not changed in recent years [1]. Furthermore, according to a study conducted in the midst of the crisis, the prevalence of current smoking was found to increase with higher levels of education, especially in women, which is in contrast to the patterns of smoking in the West [67,71]. It is well known that in the western social context smoking is more prevalent among individuals with lower education [67,71].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 76%
See 1 more Smart Citation
“…Specifically, the prevalence of smoking was quite low among the population aged ⩾65 years before the crisis and this has not changed in recent years [1]. Furthermore, according to a study conducted in the midst of the crisis, the prevalence of current smoking was found to increase with higher levels of education, especially in women, which is in contrast to the patterns of smoking in the West [67,71]. It is well known that in the western social context smoking is more prevalent among individuals with lower education [67,71].…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 76%
“…Furthermore, according to a study conducted in the midst of the crisis, the prevalence of current smoking was found to increase with higher levels of education, especially in women, which is in contrast to the patterns of smoking in the West [67,71]. It is well known that in the western social context smoking is more prevalent among individuals with lower education [67,71]. The data from RACHIOTIS et al [67] supported the findings that in western countries lower educated people smoked more than higher educated people.…”
Section: Respiratory Mortality In Greece Amid An Economic Crisismentioning
confidence: 96%
“…The patterning of smoking over time is further shaped by macro level national developments, such as economic fluctuations and social structural transformations, [11][12][13] as well as individual level sociodemographic and health-related factors. [14][15][16] The epidemic model finds support from western time trend studies suggesting that socioeconomic differences in smoking remain or even widen, [8][9][10]17 and it offers a framework and context for examining socioeconomic differences in smoking over time and across countries. Longitudinal studies following the same participants are, nevertheless, lacking although they would add to our understanding of the dynamics of both relative and absolute socioeconomic differences in smoking.…”
Section: Introductionmentioning
confidence: 99%
“…The epidemic model has been extended to include also socioeconomic differences. [8][9][10] At the early stages, the upper classes are the first to take up smoking, but over time the habit spreads disproportionately to the lower classes, with emerging socioeconomic differences. The patterning of smoking over time is further shaped by macro level national developments, such as economic fluctuations and social structural transformations, [11][12][13] as well as individual level sociodemographic and health-related factors.…”
Section: Introductionmentioning
confidence: 99%
“…Contrasting with the decline in smoking habits among men in most European countries, 33 previous studies have placed Portugal at an earlier stage (transition between stage 2 and 3) of the smoking epidemic, the prevalence being higher in men and in more educated women. [34][35][36] Additionally, there is an increasing body of evidence supporting the existence of sex differences in genetic susceptibility to air-flow obstruction and COPD.…”
Section: Discussionmentioning
confidence: 73%